Coccolithophores as proxy of seawater changes at orbital‐to‐millennial scale during middle Pleistocene Marine Isotope Stages 14–9 in North Atlantic core MD01‐2446. (12th June 2014) - Marino, Maria; Maiorano, Patrizia; Tarantino, Francesca; Voelker, Antje; Capotondi, Lucilla; Girone, Angela; Lirer, Fabrizio; Flores, José‐Abel; Naafs, B. David A.
Abstract Quantitative coccolithophore analyses were performed in core MD01‐2446, located in the midlatitude North Atlantic, to reconstruct climatically induced sea surface water conditions throughout Marine Isotope Stages (MIS) 14–9. The data are compared to new and available paleoenvironmental proxies from the same site as well as other nearby North Atlantic records that support the coccolithophore signature at glacial‐interglacial to millennial climate scale. Total coccolithophore absolute abundance increases during interglacials but abruptly drops during the colder glacial phases and deglaciations. Coccolithophore warm water taxa (wwt) indicate that MIS11c and MIS9e experienced warmer and more stable conditions throughout the whole photic zone compared to MIS13. MIS11 was a long‐lasting warmer and stable interglacial characterized by a climate optimum during MIS11c when a more prominent influence of the subtropical front at the site is inferred. The wwt pattern also suggests distinct interstadial and stadial events lasting about 4–10 kyr. The glacial increases of Gephyrocapsa margereli‐G. muellerae 3–4 µm along with higher values of Corg, additionally supported by the total alkenone abundance at Site U1313, indicate more productive surface waters, likely reflecting the migration of the polar front into the midlatitude North Atlantic. Distinctive peaks of G. margereli‐muellerae (>4 µm), C. pelagicus pelagicus, Neogloboquadrina pachyderma left coiling, and reworked nannofossils, combined with minima in total nannofossil accumulation rate, are tracers of Heinrich‐type events during MIS12 and MIS10. Additional Heinrich‐type events are suggested during MIS12 and MIS14 based on biotic proxies, and we discuss possible iceberg sources at these times. Our results improve the understanding of mid‐Brunhes paleoclimate and the impact on phytoplankton diversity in the midlatitude North Atlantic region.